A Cross Sectional Study of Alcohol Abuse among Medical Students in Upums Etawah - Vaibhav Singh; Dhiraj Kumar Srivastava; Pankaj Kumar Jain; Nawazish Ali; Nishant Singh; Abhinav Gangwar (National Journal of Community Medicine, 2020)
Introduction: Alcohol abuse among medical students has important implication. This study was conducted to determine prevalence of alcohol abuse in undergraduates of medical students and to determine the characteristics of alcohol drinking behaviour and to assess the effect on their academic performance.